An Exploratory Study to Understand Factors Associated with Health-related Quality of Life Among Uninsured/Underinsured Patients as Identified by Clinic Providers and Staff. (August 2020) - Wippold, Guillermo M.; Nmezi, Nwakaego; Williams, Jaime L.; Butler, Jacqueline; Hodge, Tanya M.
Since the release of Healthy People 2020, there has been extensive research understanding factors associated with health-related quality of life (HRQoL) among specific populations. Despite this growing body of research, little has been conducted to understand the factors associated with HRQoL among uninsured/underinsured Americans. The purposes of the present study were to assess clinic staff to determine: (1) whether there is a need to examine HRQoL among uninsured/underinsured individuals, (2) whether there is a need for tailored HRQoL-promoting interventions among uninsured/underinsured individuals, and (3) the factors associated with HRQoL among uninsured/underinsured individuals. A survey was sent to an association of 41 clinics that provides free medical services to uninsured/underinsured individuals. The majority of participants indicated that uninsured/underinsured individuals experience unique factors associated with HRQoL and that there was a need to implement tailored HRQoL-improving interventions among uninsured/underinsured individuals. The results also present the personal/contextual factors associated with HRQoL of uninsured/underinsured individuals.